The Structure of Judges 2.6-16.31 - Williams, Jay G. 1932- (1991)
The Book of Judges, far from being the product of a series of clumsy editors who simply arranged independent blocks of material, is carefully constructed according to the cycle of the solar year. Each of the twelve judges can be identified with a different tribe and each tribe with a month. Although the stories of Samson may be the most telling example, all the stories of the judges relate to the seasons of the year and their festivals. The cycle is carefully balanced according to geographical location and maternal origin of the respective tribes. The role of women (in particular, Deborah, Jephthah's daughter, and Delilah) seems to mirror the role of the earth in the agricultural cycle. Although such a cyclical interpretation of Judges does not belie the historicity of the stories, it puts the historiography of Judges in a radically new perspective.